All creatures great & small. The complete series 7 collection [videorecording (DVD)] - Timothy, Christopher; Hardy, Robert, 1925-2017; Davison, Peter, 1951-; Drinkwater, Carol; Herriot, James (BBC Video : Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2007)
The final installment of the heart-warming tale about Yorkshire veterinarian James Herriot, his wife Helen and his volatile but warm-hearted partner, Siegfried Farnon. Life at the small veterinary practice continues to challenge the partners, but through all the trials and tribulations, the social upheavals and the years gone by, friendship and family prove themselves as strong as ever.